Search for Λb0→pπ and Λb0→pK decays in pp̄ collisions at s=1.96 TeV - Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2005)
We report on a search for Λb0→pπ- and Λb0→pK- (and charge conjugate) decays in pp̄ collisions at s=1.96TeV using 193pb-1 of data collected by the CDF II experiment at the Fermilab Tevatron Collider. Data were collected using a track trigger that has been optimized to select tracks belonging to a secondary vertex that is typical of two-body charmless decays of b-flavored hadrons, including Λb0 baryons. As no Λb0 signal was observed, we set the upper limits on the branching fraction B(Λb0→ph-), where h is K or π, of 2.3×10-5 at 90% C.L. and 2.9×10-5 at 95% C.L. © 2005 The American Physical Society.